Advancing mite phylogenomics: Designing ultraconserved elements for Acari phylogeny. (27th February 2019) - Van Dam, Matthew H.; Trautwein, Michelle; Spicer, Greg S.; Esposito, Lauren
Abstract: Mites (Acari) are one of the most diverse groups of life on Earth; yet, their evolutionary relationships are poorly understood. Also, the resolution of broader arachnid phylogeny has been hindered by an underrepresentation of mite diversity in phylogenomic analyses. To further our understanding of Acari evolution, we design targeted ultraconserved genomic elements (UCEs) probes, intended for resolving the complex relationships between mite lineages and closely related arachnids. We then test our Acari UCE baits in‐silico by constructing a phylogeny using 13 existing Acari genomes, as well as 6 additional taxa from a variety of genomic sources. Our Acari‐specific probe kit improves the recovery of loci within mites over an existing general arachnid UCE probe set. Our initial phylogeny recovers the major mite lineages, yet finds mites to be non‐monophyletic overall, with Opiliones (harvestmen) and Ricinuleidae (hooded tickspiders) rendering Parasitiformes paraphyletic.